Excess fermentation and lactic acidosis as detrimental functions of the gut microbes in treatment-naive TB patients - Yunusbaeva, Milyausha; Borodina, Liliya; Terentyeva, Darya; Bogdanova, Anna; Zakirova, Aigul; Bulatov, Shamil; Altinbaev, Radick; Bilalov, Fanil; Yunusbayev, Bayazit (Frontiers in Cellular and Infection Microbiology, 2024)
The link between gut microbiota and host immunity motivated numerous studies of the gut microbiome in tuberculosis (TB) patients. However, these studies did not explore the metabolic capacity of the gut community, which is a key axis of impact on the host's immunity. We used deep sequencing of fecal samples from 23 treatment-naive TB patients and 48 healthy donors to reconstruct the gut microbiome's metabolic capacity and strain/species-level content. We show that the systematic depletion of the commensal flora of the large intestine, Bacteroidetes, and an increase in Actinobacteria, Firmicutes, and Proteobacteria such as Streptococcaceae, Erysipelotrichaceae, Lachnospiraceae, and Enterobacteriaceae explains the strong taxonomic divergence of the gut community in TB patients. The cumulative expansion of diverse diseaseassociated pathobionts in patients reached 1/4 of the total gut microbiota, suggesting a heavy toll on host immunity along with MTB infection. Reconstruction of metabolic pathways showed that the microbial community in patients shifted toward rapid growth using glycolysis and excess fermentation to produce acetate and lactate. Higher glucose availability in the intestine likely drives fermentation to lactate and growth, causing acidosis and endotoxemia.Excessive fermentation and lactic acidosis likely characterize TB patients' disturbed gut microbiomes. Since lactic acidosis strongly suppresses the normal gut flora, directly interferes with macrophage function, and is linked to mortality in TB patients, our findings highlight gut lactate acidosis as a novel research focus. If confirmed, gut acidosis may be a novel potential host-directed treatment target to augment traditional TB treatment.